Конкурентна стратегія як інструмент маркетингового менеджменту - Шевчук, Олена Юріївна; Шевчук, Елена Юрьевна; Shevchuk, Olena (My University, 2016)
UK: Стаття присвячена обґрунтуванню маркетингової конкурентної стратегії в маркетинговому менеджменті на прикладі ПрАТ «Чумак». Проаналізований стан підприємства та середовища. Сформована модель поведінки споживачів на ринку макаронів та макаронних виробів, досліджений попит та споживчі мотивації, побудована бізнес-модель підприємства, що спрямована на розробку конкурентної стратегії диференціації. EN: The article is devoted to substantiation important competitive marketing strategy in marketing management on the example of JSC "Chumak" and identify patterns in developing competitive strategies. Nowadays the problem of improvement and efficiency of enterprise management and evaluation of marketing activities are very relevant. Theoretical position to determine the nature and characteristics of competitive strategies in marketing management company. Factors macro and micro of pasta and pasta products’ market, the importance and power of influence of each factor on the pasta market. The condition of the enterprise market. The current model of consumer behavior in the market of pasta and pasta investigated demand and consumer motivation. Generalized trend of the domestic market of pasta and pasta. Grounded alternatives to the opportunities and prevent threats: increasing the production of pasta by expanding the assortment line, namely the introduction of a new product - sheets for lasagna "premium" - the segment focused on healthy lifestyle (HLS), with further access to new markets. Strategic analysis conducted by BCG, benchmarking, positioning method used - for determining the level of competitiveness of production of PJSC "Chumak" in the market of macaroni and pasta. Built a business model enterprise via GEL - factor (Great customers - the availability of dedicated customer; Easy sales - the relative ease of the sale; Long life - guaranteed longevity of the company), which leads to the conclusion that the company wisely realizes his concept of business development and market expansion.
Competitive strategy as instrument of marketing management
Keywords: конкурентна стратегія; маркетинговий менеджмент; бізнес-модель; GEL – фактори; макро- мікромаркетингове середовище; competitive strategy; marketing management; business model; GEL - factors; micro and macro marketing environment